Revisiting the stop-and-stare algorithms for influence maximization - Huang, Keke (2019)
Influence maximization is a combinatorial optimization problem that finds important applications in viral marketing, feed recommendation, etc. Recent research has led to a number of scalable approximation algorithms for influence maximization, such as TIM+ and IMM, and more recently, SSA and D-SSA. The goal of this paper is to conduct a rigorous theoretical and experimental analysis of SSA and D-SSA and compare them against the preceding algorithms. In doing so, we uncover inaccuracies in previously reported technical results on the accuracy and efficiency of SSA and D-SSA, which we set right. We also attempt to reproduce the original experiments on SSA and D-SSA, based on which we provide interesting empirical insights. Our evaluation confirms some results reported from the original experiments, but it also reveals anomalies in some other results and sheds light on the behavior of SSA and D-SSA in some important settings not considered previously. We also report on the performance of SSA-Fix, our modification to SSA in order to restore the approximation guarantee that was claimed for but not enjoyed by SSA. Overall, our study suggests that there exist opportunities for further scaling up influence maximization with approximation guarantees.